Die Haftung der Intermediäre im Internationalen Immaterialgüterrecht Vorgaben und Grenzen von Territorialitätsprinzip und Schutzlandanknüpfung - Neumann, Sophie (Abhandlungen zum Urheber- und Kommunikationsrecht, 2015)
The book addresses intermediary liability from the private international law perspective. It focuses on the law applicable to intermediary liability in cases where the offering of (internet) platforms or services enables infringement of intellectual property rights in several countries. Analysing the requirements of territoriality and of the lex loci protectionis rule, of Union law, and the legal conception of different forms of liability for enabling infringement in German, French, and US law, the book advocates a separate conflicts rule for intermediary liability departing from the lex loci protections rule and leading to the application of a single predictable law.